Wet shaking table operating parameters optimization for maximizing metal recovery from incineration bottom ash fine fraction - Muñiz Sierra, Héctor (Waste management (New York, N.Y.), 2024)
Copyright © 2023 Elsevier Ltd. All rights reserved.